Identifikasi Kepuasan Pasien Terhadap Pelayanan Klinik Utama Ramanathan di Kota Medan - Ramanathan; Susanna Halim; Alamsyah (Postgraduate, University of Mataram, 2025)
The increasing demand for beauty treatments has made customer satisfaction a critical factor in determining the success of beauty clinics. This study aims to evaluate patient satisfaction with the services provided by Klinik Utama Ramanathan in Medan. Using a quantitative approach with survey methods, data was collected from 60 respondents who had received treatments at the clinic. The analysis was based on five dimensions of service quality: tangible, reliability, responsiveness, assurance, and empathy. Results indicate that the overall patient satisfaction level is high, with the assurance dimension receiving the highest rating (4.4) and responsiveness scoring the lowest (4.1). Regression analysis revealed that assurance had the most significant impact on patient satisfaction, followed by tangible aspects, empathy, reliability, and responsiveness. Although the clinic performs well in service quality, improvements in responsiveness, such as faster response times and enhanced customer interaction, could further enhance patient satisfaction. The study highlights the importance of continuous service quality improvements in maintaining competitiveness in the beauty clinic industry.